The Council of Europe's Underrated Role in Fostering Equitable Access to Quality Health Care in Times of Pandemic - Éloïse Gennet (Harvard FXB Center for Health and Human Rights, 2024)
Different Council of Europe organs have been attentive and reactive to specific human rights issues in the COVID-19 context, quickly alerting on the risks of inequitable access to quality health care, vaccines, or medicines for vulnerable groups. Yet these reactions have mainly taken the form of nonbinding instruments such as declarations, statements, and recommendations. Although these reactions derive from the interpretation of binding Council of Europe conventions, the observance or implementation of these conventions is not always monitored. Strasbourg judges have on several occasions confirmed that European Convention on Human Rights case law must consider other international instruments, especially those of other Council of Europe organs, in order to interpret the guarantees of the convention. As a consequence, soft law rules can sometimes indirectly acquire binding force when used as an interpretation and implementation tool for binding treaties. In this paper, I examine how Council of Europe organs interpret the principle of equitable access to health care of appropriate quality in the context of a pandemic and whether and how this interpretation is being implemented within the Council of Europe's interpretation of binding treaties such as the Medicrime Convention, the European Social Charter, and the European Convention on Human Rights.